The Role of the Students of the Infallible Imams (PBUH) in Rationalist Scientific Activities in Iraq and Its Impact on Islamic Civilization in the Abbasid Era. - Jasim Mohammed Abdullah, Researcher; Seyed Aleddin Shahrokhi, supervising professor; Daryush Nazari, Associate Professor; Mojtaba Garavand, Assistant Professor (lark, 2026)
Civilization as a social phenomenon is the product of the thoughts behind it, and rationalism has always played a central role in explaining the world and shaping civilizational structures. The process of formation of Islamic civilization was carried out as a result of convergence, internal coherence, appropriate intellectual and cultural design, and the creation of necessary capabilities. The present study, with a descriptive-analytical approach and a library method, seeks to answer the question: What role did the prominent students of the infallible Imams (peace be upon them) play in Iraq, the center of the Abbasid Caliphate, in the transformation from Hadithism to rationalism, and what impact did this have on Islamic civilization? The findings of the present study indicate that the infallible Imams (peace be upon them) played a fundamental role in guiding and expanding religious rationality in Islamic civilization; by cultivating elite and outstanding students in various sciences, especially jurisprudence, philosophy, theology, and natural sciences, they set in motion the driving force that built the capacity of Islamic civilization, which was science-centered. In this regard, the most important teachings of the Imams to their students were to transform schools and scientific centers into workshops for the production of rational thought and not merely institutions for the transmission of hadith, to trace the roots of religious concepts based on logic, to call for scientific thought and debate, and to influence various scientific fields, including theology, philosophy, and empirical sciences. This rationalism not only led to strengthening the foundations of belief, but also, by influencing theological, jurisprudential, and logical sciences, became one of the main pillars of Islamic civilization of that period.